Interaction of Cucurbit[7]uril With Protease Substrates: Application to Nanosecond Time-Resolved Fluorescence Assays - Hennig, Andreas; Nau, Werner M. (Frontiers in Chemistry, 2020)
We report the use of the macrocyclic host cucurbit[7]uril (CB7) as a supramolecular additive in nanosecond time-resolved fluorescence (Nano-TRF) assays for proteases to enhance the discrimination of substrates and products and, thereby, the sensitivity. A peptide substrate was labeled with 2,3-diazabicyclo[2.2.2]oct-2-ene (DBO) as a long-lived (>300 ns) fluorescent probe and 3-nitrotyrosine was established as a non-fluorescent fluorescence resonance energy transfer (FRET) acceptor that acts as a “dark quencher”. The substrate was cleaved by the model proteases trypsin and chymotrypsin and the effects of the addition of CB7 to the enzyme assay mixture were investigated in detail using UV/VIS absorption as well as steady-state and time-resolved fluorescence spectroscopy. This also allowed us to identify the DBO and nitrotyrosine residues as preferential binding sites for CB7 and suggested a hairpin conformation of the peptide, in which the guanidinium side chain of an arginine residue is additionally bound to a vacant ureido rim of one of the CB7 hosts.